Filamentous Soil Fungi from Ny-Ålesund, Spitsbergen, and Screening for Extracellular Enzymes - Singh, Shiv M.; Singh, Sanjay K.; Yadav, Lal S.; Singh, Paras N.; Ravindra, Rasik (ARCTIC, 2012)
Soil filamentous fungi from Ny-Ålesund, Spitsbergen, were studied. A total of 30 fungal isolates were identified by morpho-taxonomy, and the identity of some morpho-taxonomically complex isolates was authenticated by ITS1-5.8S and ITS2 rDNA domain sequence similarity. The isolates belonged to 19 species under 14 genera (Acremonium, Arthrinium, Aspergillus, Cladosporium, Corynespora, Emericella, Geomyces, Mortierella, Mucor, Myrothecium, Penicillium, Phialophora, Preussia, Xylaria). To the best of our knowledge, Acremonium roseolum, Aspergillus aculeatus, Emericella nidulans, and Preussia sp. are the first northernmost records from Arctic soils. The viable fungal count in different soil samples varied from 0.5 • 104 to 2.0 • 105 g-1. Species richness in different soil samples was also calculated. Mortierella was one of the most dominant genera in Arctic soils. A temperature tolerance study was carried out for all the isolates, and representative species were screened for their extracellular enzyme activity (amylase, cellulase, phosphatase, and pectinase) at 4˚C and 20˚C. Among the 30 isolates, seven showed cellulolytic activity, two were phosphate solubilizers, three had amylolytic activity, and only one showed pectinolytic activity on solid media. CMCase (β1, 4-endoglucanase) activity was quantified in seven isolates that exhibited positive activity during preliminary screening. The records of enzyme activity for amylases, pectinases, and cellulases are the first from the fungi of Spitsbergen. The present study indicates the dominance in Ny-Ålesund of cellulolytic strains, which may serve as potent decomposers in Arctic tundra. These isolates may be used to facilitate the mineralization of cellulolytic wastes generated by human activities in colder hilly areas across the world, including the Himalayas in India. Nous avons étudié des champignons telluriques filamenteux de Ny-Ålesund, Spitzberg. Grâce à la morpho-taxonomie, nous avons identifié 30 isolats fongiques, et l’identité de certains complexes d’isolats ...